Application of botryosphaeran as a carbon black adherent on a glassy carbon electrode for the electrochemical determination of cyclobenzaprine - Scremin, Jessica; Olean-Oliveira, André; Salamanca-Neto, Carlos A.R.; Ceravolo, Graziela S.; Dekker, Robert F.H.; Barbosa-Dekker, Aneli M.; Banks, Craig E.; Teixeira, Marcos F.S.; Sartori, Elen R. (Elsevier, 2021)
The present work describes the performance of a new voltammetric sensor based on the modification of glassy carbon electrodes (GCE) with carbon black (CB) and botryosphaeran (BOT) (CB-BOT/GCE) for the electroanalytical determination of cyclobenzaprine. BOT is a fungal exocellular (1→3)(1→6)-β-ᴅ-glucan, which was used to improve the adherence of CB onto the surface of GCE. The electrochemical characterisation was performed by electrochemical impedance spectroscopy which showed an improvement in the transfer of electrons on the surface of the sensor developed in relation to the unmodified (bare) GCE. The voltammetric behaviour of cyclobenzaprine was studied using bare GCE, BOT/GCE, CB/GCE, and CB-BOT/GCE. All electrodes presented an oxidation peak (+ 1.0 V) for cyclobenzaprine, while the cyclobenzaprine peak intensity on CB-BOT/GCE was found to be 480% higher than the bare GCE. Through employing square-wave voltammetry, the analytical curve was found to be linear over the concentration range of 2.0 to 20.6 μmol L−1 (in 0.1 mol L−1 NaCl solution) with a detection limit (based on 3-sigma) of 0.63 μmol L−1. The developed electrochemical sensor exhibited excellent sensitivity and selectivity and was successfully applied for the voltammetric determination of cyclobenzaprine in pharmaceutical, biological, and environmental samples for the first time using the CB-BOT/GCE electrochemical sensing platform.
Keywords: Carbon black; Cyclobenzaprine; Fungal (1→3)(1→6)-β-ᴅ-glucan; Modified glassy carbon electrode; Serum and environment samples